2007
DOI: 10.1215/15228517-2007-013
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative thrombocytosis predicts poor survival in patients with glioblastoma

Abstract: Background: Thrombocytosis is triggered by and promotes tumor growth. The relationship between the change in circulating platelets after chemoradiation therapy (CRT) or adjuvant temozolomide (TMZ) and survival in glioblastoma remains unclear. We hypothesized that an increase in platelets after these treatments would be predictive of a shorter survival. Methods: We retrospectively reviewed data on 122 patients with newly diagnosed, pathologically proven glioblastoma who had been treated with surgery, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 63 publications
4
62
1
Order By: Relevance
“…These observations are in full agreement with the results of our animal experiments. Since the issue of the potential impact of platelets on GBM growth has recently been brought up by the observation that preoperative thrombocytosis is a predictor of poor outcome in GBM patients [32], our present results suggest much more that thrombocytosis is not the cause but rather the consequence of the growing tumors secreting thrombopoieitic factors like interleukin (IL)-6, IL-1, VEGF, macrophage and granulocyte-macrophage colony stimulating factor (M-CSF, GM-CSF), and tumor necrosis factor a (TNF-a) [46][47][48][49]. This explanation would also fit with our recent findings that platelet counts increase from normal to elevated levels in patients with GBM [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are in full agreement with the results of our animal experiments. Since the issue of the potential impact of platelets on GBM growth has recently been brought up by the observation that preoperative thrombocytosis is a predictor of poor outcome in GBM patients [32], our present results suggest much more that thrombocytosis is not the cause but rather the consequence of the growing tumors secreting thrombopoieitic factors like interleukin (IL)-6, IL-1, VEGF, macrophage and granulocyte-macrophage colony stimulating factor (M-CSF, GM-CSF), and tumor necrosis factor a (TNF-a) [46][47][48][49]. This explanation would also fit with our recent findings that platelet counts increase from normal to elevated levels in patients with GBM [33].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a negative relationship between the platelet count and survival time has been described for a large variety of malignancies [22][23][24][25][26][27][28][29][30][31]. Furthermore, it has recently been reported that an increased preoperative platelet count is significantly correlated with shorter survival in patients with newly diagnosed glioblastoma multiforme (GBM) [32] and that platelet counts in patients with GBM rise within the months and years before diagnosis of GBM [33]. However, the pathophysiological mechanisms underlying this association are not yet clear.…”
mentioning
confidence: 99%
“…Tumor-related leukocytosis was deWned as a pretreatment white blood cell (WBC) count >10 £ 10 3 cells/ l without known inXammatory or infectious diseases, and tumorrelated thrombocytosis was deWned as a pretreatment platelet count >400 £ 10 3 cells/ l without known inXammatory conditions (Kasuga et al 2001;Pedersen and Milman 2003;Brockmann et al 2007;Sugitani et al 2001). To determine whether monocytosis is a prognostic marker of head and neck cancer, a monocyte count >1,000 cells/ l was deWned as monocytosis.…”
Section: Dewnition Of Tumor-related Leukocytosis Monocytosis Anemiamentioning
confidence: 99%
“…Pretreatment anemia is associated with shorter survival for patients with lung carcinoma (Caro et al 2001), cervical carcinoma (Caro et al 2001;Dunst et al 2003), head and neck cancer (Becker et al 2000;Caro et al 2001;Rudat et al 1999;Baghi et al 2008), lymphoma (Caro et al 2001), prostate carcinoma (Caro et al 2001), and esophageal cancer (Rades et al 2005). Pretreatment thrombocytosis indicating the abnormally high level of platelets, has been reported to be associated with poor prognosis for patients with lung carcinoma Milman 1996, 2003), glioblastoma (Brockmann et al 2007), esophageal carcinoma (Shimada et al 2004), breast cancer (Taucher et al 2003), gastric carcinoma (Ikeda et al 2002), hepatocellular carcinoma (Chen et al 2005), pancreas cancer (Suzuki et al 2004), renal cell carcinoma (Gogus et al 2004), and oral squamous cell carcinoma (Lu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytosis was reported to herald poor prognosis in patients with various cancers, ranging from ovarian carcinoma [20] through glioblastoma [22] to breast [8], stomach [7], and colorectal cancer [6]. To explain the adverse prognostic significance of thrombocytosis, it was speculated that platelets may protect the circulating tumor cells from attacks by the patient's immune system, thereby promoting metastatic disease [23,24].…”
Section: Discussionmentioning
confidence: 99%